2020
DOI: 10.9755/ejfa.2020.v32.i4.2087
|View full text |Cite
|
Sign up to set email alerts
|

Camel meat marketing and camel meat marketplace in the Algerian northern Sahara-case of the region of Souf-

Abstract: A field survey involving 62 camel butchers from Souf region the Algerian northern Sahara was implemented   in   order to establish a typology of camel butcher and collect   data   on camel meat marketing, the diversity in marketing practices and camel meat marketplace. The collected data allowed to identify 4 homogeneous groups of butchers well distinguished between them after cluster analysis. (specialized young camel butchers, non-specialized rural butchers, traditional non-specialized urban butchers, modern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…This will go a long way in guaranteeing sustainable production of camels which could contribute to the gross domestic products (GDPs) of African countries. Similar submissions have been made on the need for herders, middlemen, the cooperatives and the governments to jointly promote camel meat and milk businesses ( Gebremichael et al, 2019 ; Zakaria et al, 2020 ; Kena, 2022 ; Oselu et al, 2022 ).…”
Section: Pathways Towards Sustainable Camel Production and Conservati...mentioning
confidence: 75%
“…This will go a long way in guaranteeing sustainable production of camels which could contribute to the gross domestic products (GDPs) of African countries. Similar submissions have been made on the need for herders, middlemen, the cooperatives and the governments to jointly promote camel meat and milk businesses ( Gebremichael et al, 2019 ; Zakaria et al, 2020 ; Kena, 2022 ; Oselu et al, 2022 ).…”
Section: Pathways Towards Sustainable Camel Production and Conservati...mentioning
confidence: 75%
“…This allows access to meat proteins for the often most disadvantaged populations and ensures camel meat a certain competitiveness. In a recent study, Brahimi et al (2020) confirmed that the consumption of camel meat is less efficient in its environment (Algerian northern Sahara). These authors suggested in-depth studies on the sector to identify the bottlenecks invalidating the promotion of the consumption of camel meat.…”
Section: Camel Meat As a Substitute For Other Red Meatsmentioning
confidence: 89%
“…Consumer motivations and barriers for buying camel meat were further investigated via the survey approach. Previous study is available in the literature regarding small ruminants’ meat consumer preferences ( Brahimi et al 2020 ). This study was designed to deepen the understanding of consumers’ perceptions of different meats, as well as the motivations and barriers faced by consumers when approaching these products.…”
Section: Camel Meat Terminology and Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fermented or unfermented drying, brining and smoking of cameline meat are common traditional practices, especially in Algeria and Morocco [15]. Indeed, in some countries in order to promote this species, cameline meat is transformed into hamburgers, patties, sausages, cashir [8,[16][17][18][19].…”
Section: Camel Meat Consumption and Meat Products In The World And In...mentioning
confidence: 99%